Cells in Human Milk: State of the Science. (May 2013) - Hassiotou, Foteini; Geddes, Donna T.; Hartmann, Peter E.
Reflecting millions of years of adaptation and optimization, milk is unique to the species that produces it and for the young of which it is intended, with large variations in both lactation strategies and milk composition existing among different mammalian species. Despite this, milk has the consistent function of providing nourishment, protection, and developmental programming to the young, with short- and long-term effects. Among its components that confer these functions, breast milk contains maternal cells, from leukocytes to epithelial cells of various developmental stages that include stem cells, progenitor cells, lactocytes, and myoepithelial cells. Although in the first 150 years since their discovery, breast milk cells were mostly studied for their morphological traits, technological advances in the last decade have allowed characterization of breast milk cell types at the protein and messenger RNA levels. This is now paving the way for investigation of the functions of these cells in the breastfed infant and the use of breast milk as a tool to understand the normal biology of the breast and its pathologies. This review summarizes the current knowledge of breast milk cellular heterogeneity and discusses future prospects and potential applications.